YscU, a Yersinia enterocolitica inner membrane protein involved in Yop secretion. - Allaoui, A (1994)
Pathogenic yersiniae secrete antihost Yop proteins by a recently discovered secretion pathway which is also encountered in several animal and plant pathogens. The components of the export machinery are encoded by the virA (lcrA), virB (lcrB), and virC (lcrC) loci of the 70-kb pYV plasmid. In the present paper we describe yscU, the last gene of the virB locus. We determined the DNA sequence and mutated the gene on the pYV plasmid. After inactivation of yscU, the mutant strain was unable to secrete Yop proteins. The topology of YscU was investigated by the analysis of YscU-PhoA translational fusions generated by TnphoA transposition. This showed that the 40.3-kDa yscU product contains four transmembrane segments anchoring a large cytoplasmic carboxyl-terminal domain to the inner membrane. YscU is related to Spa40 from Shigella flexneri, to SpaS from Salmonella typhimurium, to FlhB from Bacillus subtilis, and to HrpN from Pseudomonas solanacearum.